2010
DOI: 10.1093/molehr/gaq023
|View full text |Cite
|
Sign up to set email alerts
|

cAMP efflux from human trophoblast cell lines: a role for multidrug resistance protein (MRP)1 transporter

Abstract: Cyclic adenosine 3'-5'-monophosphate (cAMP) is a second messenger, which exerts an important role in the control of human first-trimester trophoblast functions. In the present study we demonstrate the existence of a mechanism that is able to extrude cAMP from trophoblast-derived cell lines, and show evidence indicating the involvement of multidrug resistance protein (MRP) 1, a transporter belonging to the ATP-binding cassette family, in cAMP egress. MRP1 is expressed in trophoblast cell lines and cAMP efflux i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…1 and 2) reveals critical differences between their respective kinetics. Intracellular cAMP levels quickly plateau and subsequently return to basal levels, whereas extracellular cAMP levels continue to increase over extended time periods, a pattern that has also been observed in many other cell models (Penit et al, 1974;Doore et al, 1975;Brunton and Mayer, 1979;Hamet et al, 1989;Andric et al, 2006;Biondi et al, 2010). The different patterns of cAMP accumulation result primarily from differences in the efficiency of cAMP degradation.…”
mentioning
confidence: 65%
“…1 and 2) reveals critical differences between their respective kinetics. Intracellular cAMP levels quickly plateau and subsequently return to basal levels, whereas extracellular cAMP levels continue to increase over extended time periods, a pattern that has also been observed in many other cell models (Penit et al, 1974;Doore et al, 1975;Brunton and Mayer, 1979;Hamet et al, 1989;Andric et al, 2006;Biondi et al, 2010). The different patterns of cAMP accumulation result primarily from differences in the efficiency of cAMP degradation.…”
mentioning
confidence: 65%
“…In fact, it is important to emphasize that efflux of cAMP/ cGMP seems to be a widespread signaling mechanism (Hofer and Lefkimmiatis, 2007;Sager and Ravna, 2009) reported in vascular smooth muscle cells (Dubey et al, 1996), cardiac fibroblasts (Dubey et al, 2001), oviduct cells (Cometti et al, 2003), kidney (Jackson and Raghvendra, 2004;Dubey et al, 2010), adipose tissue (Strouch et al, 2005) gastrointestinal tract (Giron et al, 2008), human placenta explants (Biondi et al, 2010), astrocytes, and microglial cells (Verrier et al, 2011). Thus, the extracellular cAMP-adenosine pathway may represent a general autocrine and/or paracrine mechanism that indirectly modulates the signaling triggered by distinct receptors coupled to G s proteins, qualifying cyclic nucleotides as extracellular third messengers, and the extracellular cAMP-adenosine signaling pathway as a potential pharmacological target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is involved in the transport of both endogenous and exogenous compounds [48]. Cyclic adenosine monophosphate (cAMP) is a substrate of MRP1, and is involved in certain syncytiotrophoblast functions [92]. Interestingly, expression of MRP1 in immortalized placental trophoblast cells was shown to be modulated by interleukin-1β and estrone [92].…”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%
“…Cyclic adenosine monophosphate (cAMP) is a substrate of MRP1, and is involved in certain syncytiotrophoblast functions [92]. Interestingly, expression of MRP1 in immortalized placental trophoblast cells was shown to be modulated by interleukin-1β and estrone [92]. It was shown that MRP1 is also partially responsible for the transport of methyl mercury to the fetal circulation, which explains the higher levels of methyl mercury in umbilical cord blood in comparison to maternal blood [93].…”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%
See 1 more Smart Citation